2004
DOI: 10.1021/ja045445s
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective RNA Cleavage by DNA Bearing a Base Pair-Mimic Nucleoside

Abstract: We have synthesized the deoxyadenosine derivative tethering a phenyl group (X), which mimics the Watson-Crick A/T base pair. The RNA/DNA hybrid duplexes containing X in the middle of the DNA sequence showed a similar thermal stability regardless of the ribonucleotide species (A, G, C, or U) opposite to X, probably because of the phenyl group stacking inside of the duplex accompanied by the opposite ribonucleotide base flipped in an extrahelical position. The RNA strand hybridized with the DNA strand bearing X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…The sugar-phosphate backbone of RNA perturbed due to the unstacking conformation can be preferentially hydrolyzed as a consequence of specific base catalysis at the site adopting the in-line attack arrangement [52, 53]. Indeed, we found highly site-selective cleavage at any ribonucleotide base opposite A X in an RNA/DNA duplex [54]. The RNA-hydrolyzing activity agrees with the base flipping model in which A X forces the opposite base to flip out in an unstacked position (Figure 6(c)).…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 99%
“…The sugar-phosphate backbone of RNA perturbed due to the unstacking conformation can be preferentially hydrolyzed as a consequence of specific base catalysis at the site adopting the in-line attack arrangement [52, 53]. Indeed, we found highly site-selective cleavage at any ribonucleotide base opposite A X in an RNA/DNA duplex [54]. The RNA-hydrolyzing activity agrees with the base flipping model in which A X forces the opposite base to flip out in an unstacked position (Figure 6(c)).…”
Section: The Base Pair Analogs Of a Base Pair-mimic Structurementioning
confidence: 99%
“…The T m (melting temperature) values among the natural duplexes containing A/A, A/G, A/C, and A/U pairs differed by 12.9°C. 31 The large difference was due to the formation of A/U WatsonÍCrick base pairs and single mismatch pairs of A/A, A/G, and A/C in the middle of the RNA/DNA duplex. In contrast, the T m values of duplexes containing A phe in place of A to form A phe /A, A phe /G, A phe /C, and A phe /U pairs were almost the same (only 0.8°C differences in their T m values).…”
Section: õ3mentioning
confidence: 99%
“…We observed that the RNA strand was efficiently hydrolyzed on the 3¤-side of the ribonucleotide opposite A phe . 31 Importantly, the RNA cleavage was highly site-selective, and any RNA sequence was cleaved when hybridizing with DNA containing A phe . The RNA-hydrolyzing activity suggests that A phe stacks into the duplex stably and rigidly and that the ribonucleotide opposite A phe flips into an unstacked position regardless of the nucleotide species (Figure 6c).…”
Section: õ3mentioning
confidence: 99%
“…Bulky non-natural nucleobase (A-T base-pair mimic) was introduced to sequence-recognizing DNA. The phosphodiester linkage of RNA substrate, which is adjacent to the nucleobase opposite to the mimic, was cleaved by Mg(II) [54]. It would be also possible that, in some of previously reported artificial ribonucleases, the target phosphodiester linkages were in fact activated by non-covalent interactions of substrate RNA with the additives and this "pinpoint activation" exerted notable effects on the site-selective RNA scission.…”
Section: Other Non-covalent Systems Employing "Pinpoint Activator"mentioning
confidence: 99%